CARA SISWA KRISTEN MENGATASI PENINGKATAN STRES PADA MASA PANDEMI - Intan Suriyanti (UPPM Sekolah Tinggi Teologi Tabgha Batam, 2022)
This Article provides an overview of how to overcome the increased stress that occurs in students during a pandemic. This stress occurs due to new habits and new way of learning methods caused by current global conditions due to many restriction. As a person who has Christian faith, Christian students are expected to be able to overcome the stresses of life they experience by approaching God with gratitude for all the goodness of the Lord Jesus Christ. So that in any situation, a student as the nation's next generation and is learning various things in this life will actually progress and develop. By communicating with Allah through worship, students are expected to have the right relationship and it is not just a religious ritual, but also a lifestyle that colors hearts, thoughts, words and behavior. So that any condition that will happen in the future, even though under conditions of limitations each student can study hard and diligently even the pressure can strengthen his faith, so that Christian students can come out as winners in facing this pandemic.